PENGGUNAAN MEDIA PEMBELAJARAN PJOK OLEH GURU PJOK DI SEKOLAH DASAR - Eka Lisa Fitriana (Jayabama: Jurnal Peminat Olahraga, 2023)
This research aims to find out how high the use of PJOK learning media is by PJOK teachers in elementary schools in Kretek District, Bantul Regency. This research is quantitative descriptive. The method used in this research is a survey method, the instrument is a questionnaire. The subjects in this research were all PJOK teachers in elementary schools in Kretek District, totaling 14 people. The data analysis technique uses quantitative descriptive analysis presented in percentage form. The results of this research show that the use of PJOK learning media by PJOK teachers in elementary schools in Kretek District, Bantul Regency is in the "very low" category 7.14%, "low" 28.57%, "fair" 21.43%, “high” 42.86 % and “very high” 0 %,.